2009
DOI: 10.1002/asl.210
|View full text |Cite
|
Sign up to set email alerts
|

The role of air turbulence in warm rain initiation

Abstract: Quantitative parameterization of turbulent collision of cloud droplets represents a major unsolved problem in cloud physics. Here a hybrid direct simulation tool is used specifically to quantify the turbulent enhancement of the gravitational collision-coalescence. Simulation results show that air turbulence can enhance the collision kernel by an average factor of about 2, and the observed trends are supported by scaling arguments. An impact study using the most realistic collection kernel suggests that cloud t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 33 publications
4
66
0
Order By: Relevance
“…The collection kernel K is calculated from the traditional collision efficiencies as given by Hall (1980) and includes turbulence effects by an enhancement factor for the collision efficiency by Wang and Grabowski (2009) as well as parameterizations for particle relative velocities and changes in the particle radial distribution based on Ayala et al (2008). These turbulence effects are steered by the kinetic energy dissipation rate calculated in the LES subgrid-scale model (Riechelmann et al, 2012).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection kernel K is calculated from the traditional collision efficiencies as given by Hall (1980) and includes turbulence effects by an enhancement factor for the collision efficiency by Wang and Grabowski (2009) as well as parameterizations for particle relative velocities and changes in the particle radial distribution based on Ayala et al (2008). These turbulence effects are steered by the kinetic energy dissipation rate calculated in the LES subgrid-scale model (Riechelmann et al, 2012).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These turbulence effects are steered by the kinetic energy dissipation rate calculated in the LES subgrid-scale model (Riechelmann et al, 2012). The parameterizations by Ayala et al (2008) are a direct function of ; the tabulated values of the enhancement factor for the collision efficiency by Wang and Grabowski (2009) are interpolated to the present value of . The Eqs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In section 4.1 we consider its effect on condensational growth. Droplet growth by gravitational collision-coalescence only becomes efficient once a certain fraction of droplets reaches 30-50 µm in radius (Pruppacher and Klett, 1997, sections 14.5, 15.1-15.3;Xue et al, 2008;Wang and Grabowski, 2009;Grabowski and Wang, 2009). The rapid growth of droplets from 15 to 50 µm remains difficult to explain.…”
Section: Small-scale Turbulence and Cloud Microphysicsmentioning
confidence: 99%
“…When the effect of turbulence on collision efficiency is also considered, Wang and Grabowski (2009) concluded that the warm rain initiation time could be reduced up to a factor of two. Using the same turbulent collision kernel and a rising adiabatic parcel model that combines droplet activation, diffusional growth and turbulent collision-coalescence, Grabowski and Wang (2009) showed that air turbulence could reduce the warm rain initiation time by 25-40%.…”
Section: Impact Of Turbulent Collision-coalescence On Droplet Growthmentioning
confidence: 99%
“…The collection kernel developed by Ayala et al (2008b) and Wang and Grabowski (2009) is used (hereafter the AW kernel), in which the effects of turbulence from relative velocity, preferential concentration, and the enhanced collision efficiency are parameterized as a function of the dissipation rate e and the Taylor-microscale Reynolds number. The Hall kernel (Hall 1980), which considers only gravitational collision, is also used for comparison.…”
Section: Model Descriptionmentioning
confidence: 99%